AJUSTE GENITAL EN LA COPULA DE THYNNINAE (HYMENOPTERA, TIPHIIDAE) (Acta Entomológica Chilena, 2022)
Aspeas of che mechanics of phorectic copulation of Eiaph roptrra unlmejormis (Halidav) are described.Various parts of the complex aedeagus. che eight meiasomal slernum of the male and ihe teníalecopulatory pouch, make the locking mechanism possible. When protruding, the eight slernum roíalesand push the male genitalia into the female. The copulatory pouch is formed by protrusion of the laststemum of the female, il has a ventral space for the aedeagus. lateral pouches for the flap-like aedeagalstruaures and a dorsal sclerotized bar for the articulated penis valvae.